"High runs" of a ship in multi-chromatic seas. (1st July 2016) - Themelis, Nikos; Spyrou, Kostas J.; Belenky, Vadim
Abstract: When a ship operates in steep irregular waves, it can attain, in intermittent time intervals, abnormally high speed, due to waves' effect. Such events may occur in following seas and they will be called hereafter "high runs". Investigations have been carried out for this peculiar type of ship motion, in three directions: firstly, the statistics of high runs are calculated by numerical simulation, exploring, in particular, their dependence on the wave spectrum and the sea state. Secondly, a rather neglected up to now analytical method, proposed in the 60 s by Grim, for the quantification of the probability of high run occurrence, is assessed, against a direct numerical approach. Finally, the actual velocity of a ship in high run incidents is investigated. Suitable metrics are applied on the difference between characteristic velocity values associated with wave's form, and surge velocity, during high runs. Graphical abstract: Comparison of probabilities of high run duration between simulation statistics and Grim's method. Highlights: Involuntary high-speed-runs of a ship in following seas are studied. The statistical character of high runs is revealed, for various sea-states. Comparison of numerical and analytical predictions of the statistics is performed. The mean velocity during high run incidents is investigated.